PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN METODE PETA PIKIRAN - NURTIANI, AYI TEIRI (PPs UNJ, 2012)
The aims of this research are to know the upgrading of learning outcome in islamic study by use of mind method and are there any increase of grade first class elementary student capalibity of learning outcome in islamic studi after giving the learning outcome in islamic study by use of mind map method. 24 students of first class at Amaliah Elementary Ciawi-Bogor are the subject of this research. This research used action research method according to Kemmis and Mc. Taggart that consist of four step : 1) plan, 2) action, 3) observation and 4) reflection. The data was collected by filed notes, interview, observation, test an documentation. The data was analyzed by outcome in islamic study by use om mind map method could increase capability of first class elementary students. Whereas the learning outcome in islamic study consist of cognitive, afective, and psikomotor.Keywords: learning aoutcome in islamic study, mind map method